More pistachio nuts for improving the blood lipid profile. Systematic review of epidemiological evidence. - Lippi, Giuseppe; Cervellin, Gianfranco; Mattiuzzi, Camilla (Acta Biomedica Atenei Parmensis, 2016)
Recent evidence suggests that regular intake of nuts may be associated with reduction of all-cause mortality, especially cardiovascular deaths. Among all types of nuts, pistachio displays the most favorable dietary composition. Therefore, we searched Medline and ISI Web of Science to identify interventional studies which evaluated changes of conventional blood lipids after replacing part of normal caloric intake with pistachio nuts in humans. Overall, 9 studies were finally included in our systematical literature review (4 randomized crossover, 3 randomized controlled and 3 prospective). In 6/9 (67%) interventional studies total cholesterol and low-density lipoprotein cholesterol (LDL-C) decreased, whereas high-density lipoprotein cholesterol (HDL-C) increased. In all studies total cholesterol/HDL-C ratio (7/7; 100%) and LDL-C/HDL-C ratio (6/6; 100%) decreased after replacing caloric intake with pistachio nuts for not less than 3 weeks. A significant reduction of triglycerides could only be observed in 2 out of 8 studies (25%). Even more importantly, in no interventional study the intake of pistachio nuts was associated with unfavorable changes of the lipid profile. The results of our literature search provide solid evidence that intake of pistachio nuts may exerts favorable effects on the traditional blood profile, provided that their consumption does not increase the habitual or recommended daily caloric intake. It seems also reasonable to suggest that further studies aimed to investigate the favorable effects of nuts on human diseases should distinguish between one type and the others, since the different nuts exhibit unique dietary composition and may hence produce distinctive biological effects in humans.